Improved mine planning using geostatistics and fractal geometry for geologic modeling - Kuchta, Mark E. (Luleå tekniska universitet, 1990)
In planning a mining operation, the geologic model of the orebody forms the basis for the layout of the development workings and for the eventual layout for the production mining. The problem faced by the mine planning and geology team is to determine what level of sampling is necessary in order to accurately construct the geologic model of the orebody such that mining can be done at a low cost and without surprises. This thesis summarizes techniques for orebody construction based on geostatistics. In addition to estimating the position of a surface from the available exploration drill hole data, the accuracy of the estimates is also obtained. An economic model is outlined which compares the cost of additional exploration drilling to the potential cost benefits that result from better location of the mine development and production workings, thus allowing the optimal level of exploration to be determined. Principles of fractal geometry are also used to simulate geologic surfaces, and to construct a model for estimating the amounts of ore loss and dilution that may occur as a result of the deviations of the geologic model from the true orebody surfaces. An economic model for determining the optimal level of sampling such that ore loss and waste rock dilution is minimized is also outlined. The use of the orebody construction techniques and the two economic models is illustrated using data from LKAB's Malmberget mine, Sweden. Godkänd; 1990; 20070429 (ysko)